Emotion-focused perspective on breast cancer patients' experiences of comorbid anxiety and depression: a qualitative case analysis of three clients' in-session presentations. (2nd April 2020) - Hissa, Joana; Connolly, Allison; Timulak, Ladislav; Hession, Natalie
ABSTRACT: The current study is a qualitative, descriptive-interpretative study that utilizes an emotion-focused therapy (EFT) theoretical framework as the basis of interpretation of clients' experiences of co-morbid anxiety and depression among three women with breast cancer. The study consists of analysis into the clients' in-session presentation of their difficulties. The study uses a multiple case study observational qualitative design. In total, 18 video-recorded therapy sessions from 3 clients were used for analysis. Sessions were analyzed utilizing an EFT case conceptualization framework. Findings illustrate common themes across cases, organized within EFT conceptualization domains; these include triggers of emotional pain, such as hurtful relationships with close ones and cancer diagnosis/treatment; problematic self-treatment like self-blame and/or excessive worrying; global distress evidenced in the form of anxiety and depression symptoms; emotional and behavioral avoidance strategies such as interruption of emotions, self-distraction and avoidance of activities potentially triggering of painful emotions. The underlying core pain takes the form of sadness/loneliness, shame and fear, and points to corresponding unmet needs (e.g. to be loved, to be recognized, to be protected). The discussion focuses on presenting the findings in the context of psycho-oncology and EFT theory.